Comparison of the ERP-Based BCI Performance Among Chromatic (RGB) Semitransparent Face Patterns - Li, Shurui; Jin, Jing; Daly, Ian; Zuo, Cili; Wang, Xingyu; Cichocki, Andrzej (Frontiers in Neuroscience, 2020)
Brain-computer interfaces (BCIs) provide a direct communication pathway, that is independent of muscular control, for individuals with communication disorders. The event-related potential (ERP)-based BCI system is the most commonly used type of BCI. Its’ performance is generally assessed by classification accuracy and information transfer rate (ITR). To date, many researchers have designed optimized visual paradigms based on the face stimuli to elicit ERPs during BCI control. These ERPs are not limited to P300 components and also include other types of ERP, which are used to improve the performance of system. Additionally, previous studies have also shown that color stimuli may be used to improve the performance of ERP-based BCIs. In this study, we explore the effect of red semitransparent face (RSF), green semitransparent face (GSF) and blue semitransparent face (BSF) patterns on the BCI performance from the combination of color and transparency perspective. The result indicated that the RSF pattern achieved the highest online averaged accuracy with 93.89%, followed by the GSF pattern with 87.78%, and the lowest was the BSF pattern with 81.39%. Furthermore, significant differences in classification accuracy and ITR were found between RSF and GSF (p<0.05) and between RSF and BSF patterns (p<0.05).